Otitis media with effusion in preschool children with adenoid hypertrophy: Risk factors and nursing care - Runyi Hu; Lifang Xia; Chenchen Shi; Ying Zhou; Xiaowen Guo (Wiley, 2024)
Abstract Aim To evaluate the influencing factors of otitis media with effusion (OME) in children with adenoid hypertrophy and to provide evidence for clinical treatment and care of children with adenoid hypertrophy. Design A retrospective study. Methods Preschool children with adenoid hypertrophy treated in our hospital from 1 January 2021 to 30 July 2022 were included. We analysed the characteristics of OME and non‐OME children with adenoid hypertrophy. Pearson correlation analysis and logistic regression analysis were performed to evaluate the risk factors for OME in children with adenoid hypertrophy. Conclusion A total of 166 children with adenoid hypertrophy were included; the incidence of OME in children with adenoid hypertrophy was 34.94%. The incidence of OME decreased significantly with the increase in age (p = 0.014). Logistic regression analysis showed that age < 3 years (OR = 3.149, 95%CI: 2.812-3.807) and duration of adenoid hypertrophy ≥12 months (OR = 2.326, 95%CI: 2.066-2.612) were the risk factors of OME in children with adenoid hypertrophy (all p < 0.05). Patient Contribution The incidence of adenoid hypertrophy with OME is high in preschool children, and it is related to the age and duration of adenoid hypertrophy.